A new species of Cascabela (Apocynaceae; Rauvolfioideae, Plumerieae) from Michoacán, Mexico - Alvarado-Cardenas, Leonardo Osvaldo; Soto Núñez, José Carmen (Phytotaxa, 2014)
A new species of Cascabela endemic to the Balsas Basin from Michoacán, Mexico is described and illustrated. Cascabela balsaensis can be separated from all known species of the genus because of its elliptic-lanceolate to lanceolate and subcoriaceous leaves with dense pubescence, very small calycine colleters, and shorter corollas. In addition, we provide an evaluation of conservation, a map of distribution, and a species key.